Depression and metabolism: linking changes in leptin and ghrelin to mood - Lutter, Michael (Biology Reports Ltd, 2009)
Major depressive disorder is associated with an elevated risk of numerous metabolic disturbances, including obesity, metabolic syndrome, insulin-dependent diabetes mellitus type II, and death after myocardial infarction. Several recent papers also indicate that disturbances of mood may alter peripheral signaling pathways that regulate metabolic processes, including those involving leptin and ghrelin.